How do environmental regulations affect industrial dynamics? Evidence from China's pollution-intensive industries. (February 2017) - Zhou, Yi; Zhu, Shengjun; He, Canfei
Abstract: Pollution haven hypothesis (PHH) and porter hypothesis (PH) offer two different perspectives to understand the relationship between industrial dynamics and environmental regulations. This paper seeks to move beyond existing studies that are based on either the PHH or the PH while neglecting the other, towards an analytical framework that not only pays more attention to the ways in which the PHH and the PH co-exist, but also acknowledges the role of firm heterogeneity and local government intervention. Based on a firm-level industrial dataset and a dataset on China's polluting firms, this paper studies the relationship between environmental regulations and industrial dynamics in China's pollution-intensive industries at the firm level. Empirical results confirm the co-existence of the PH and the PHH. Furthermore, firm heterogeneity and government intervention both have the potential to inflect the relationship between environmental regulations and industrial dynamics.